2014
DOI: 10.1017/s1751731114000494
|View full text |Cite
|
Sign up to set email alerts
|

Influence of estrus on dry matter intake, water intake and BW of dairy cows

Abstract: The objectives of this study were to analyze whether dry matter intake (DMI), water intake (WI) and BW were influenced by estrus. A second objective was to determine whether correlations exist among these traits in non-estrous days. Data collection included 34 Holstein-Friesian cows from the research farm 'Haus Riswick' of the Agricultural Chamber North Rhine-Westphalia, Germany. On an individual basis, daily DMI and daily WI were measured automatically by a scale in the feeding trough and a WI monitoring syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
2
15
1
1
Order By: Relevance
“…The effects of estrus on feeding behavior vary in different studies: Lukas et al (2008) described an increased DMI during estrus, Maltz et al (1997) and Reith et al (2014) found a decrease in DMI, and De Silva et al (1981) found no effect on DMI. In addition, a decrease in rumination time during estrus was described by Reith and Hoy (2012).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of estrus on feeding behavior vary in different studies: Lukas et al (2008) described an increased DMI during estrus, Maltz et al (1997) and Reith et al (2014) found a decrease in DMI, and De Silva et al (1981) found no effect on DMI. In addition, a decrease in rumination time during estrus was described by Reith and Hoy (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Reith et al (2014) affirmed the increase of cows´ locomotion activity related to the estrus beginning of the Holstein and Fleckvieh breed on average by 38 %. The comparable results of the increased locomotion activity of Holstein dairy cows in the estrus period in comparison with the reference period before estrus were detected also by our research (32.2 %).…”
Section: Resultsmentioning
confidence: 52%
“…According to Lopez -Gatius et al (2005) each increase of efficiency by 1 kg decreases the locomotion activity during estrus by -1.6 %. Similarly, Reith et al (2014) claim that the increase of activity of high milk producing dairy cows (with the daily production more than 40 kg of milk) was less noticable in comparison with the dairy cows of a lower milk production. However, based on the experiments Arney et al (1994) did not detect a significant impact of the milk production on the level of the dairy cows´ locomotion activity during estrus.…”
Section: Resultsmentioning
confidence: 99%
“…Reith and Hoy (2012) evaluated 265 estrus events, finding that rumination on the day of estrus decreased 17 % (74 min), but with large variation between herds (14 to 24 %). In a follow-up study that looked at 453 estrous cycles, rumination time decreased 19.6 % (83 min) on the day of estrus (Reith et al, 2014). Pahl et al (2015) also found a decrease in rumination on the day of (19.3 %) and the day before (19.8 %) inseminations leading to pregnancy.…”
Section: Feeding and Rumination Timementioning
confidence: 96%
“…The effects of estrus on feeding behavior vary in different studies, for example Maltz et al (1997) and Reith et al (2014) described a decrease in daily matter intake (DMI), Lukas et al (2008) observed an increased in DMI during estrus, and de Silva et al (1981) found no effect on DMI.…”
Section: Feeding and Rumination Timementioning
confidence: 99%